First search for CP violation in tau lepton decay - Anderson, S; Kubota, Y; Lee, S; O'Neill, J; Poling, R; Riehle, T; Smith, A; Alam, MS; Athar, S; Ling, Z; Mahmood, A; Timm, S; et al. (1998)
We have performed the first search for CP violation in tau lepton decay. CP violation in lepton decay does not occur in the minimal standard model but can occur in extensions such as the multi-Higgs doublet model. It appears as a characteristic difference between the τ- and τ+ decay angular distributions for the semileptonic decay modes such as τ- → K0π-ν. We define an observable asymmetry to exploit this and find no evidence for any CP violation.